2008
DOI: 10.1111/j.1365-294x.2007.03645.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin and number of founders in an introduced insular primate: estimation from nuclear genetic data

Abstract: Cynomolgus macaques (Macaca fascicularis) were introduced on the island of Mauritius between 400 and 500 years ago and underwent a strong population expansion after a probable initial founding event. However, in practice, little is known of the geographical origin of the individuals that colonized the island, on how many individuals were introduced, and of whether the following demographic expansion erased any signal of this putative bottleneck. In this study, we asked whether the current nuclear genome of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 31 publications
(39 reference statements)
6
55
1
2
Order By: Relevance
“…The Mauritian animals, purportedly introduced from Java as recently as the seventeenth or eighteenth centuries Tattersall 1981, 1986), reflect strong founder effects by exhibiting approximately one fourth of all the alleles found in long-tailed macaques and in both macaque species, respectively. The low Mauritian diversity at STR (as observed in this study as well as that by Bonhomme et al 2008), MHC (Kawamoto et al 2008) and mtDNA ) loci and the absence of Y chromosomal variation Coke 2007, Kawamoto et al 2008) have been attributed to small founder representation and subsequent rapid population expansion , Kawamoto et al 2008, Bonhomme et al 2008. In contrast to the findings here that the Mauritian and Indonesian animals are indeed genetically distinct, Bonhomme et al (2008) and Kawamoto et al (2008) reported a higher degree of similarity between the Mauritian and Javan animals suggesting that the founders of the former population actually descend from Javanese ancestors.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The Mauritian animals, purportedly introduced from Java as recently as the seventeenth or eighteenth centuries Tattersall 1981, 1986), reflect strong founder effects by exhibiting approximately one fourth of all the alleles found in long-tailed macaques and in both macaque species, respectively. The low Mauritian diversity at STR (as observed in this study as well as that by Bonhomme et al 2008), MHC (Kawamoto et al 2008) and mtDNA ) loci and the absence of Y chromosomal variation Coke 2007, Kawamoto et al 2008) have been attributed to small founder representation and subsequent rapid population expansion , Kawamoto et al 2008, Bonhomme et al 2008. In contrast to the findings here that the Mauritian and Indonesian animals are indeed genetically distinct, Bonhomme et al (2008) and Kawamoto et al (2008) reported a higher degree of similarity between the Mauritian and Javan animals suggesting that the founders of the former population actually descend from Javanese ancestors.…”
Section: Discussionmentioning
confidence: 50%
“…The gradual loss of genetic diversity might have occurred as new areas on the mainland were colonized by the species. However, Tosi et al's data (2003), along with that of Street et al (2007) and Bonhomme et al (2008) imply that the long-tailed macaques in Indochina represent a very old population because of the large number of private alleles it retains, supporting the alternative hypothesis that the long-tailed macaques originated instead in Indochina. The fractured landscape of the Indonesian archipelago, rife with significant physical barriers that isolate wildlife populations, might then have caused the Indonesian macaques to diverge into new subspecies.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The macaque population of this isolated Indian Ocean island was characterized by only seven extended MHC haplotypes, together with recombinants between these ancestral haplotypes. As with the Caribbeanorigin vervets, this macaque population was founded in the 17th century by a small number of monkeys introduced by Europeans (Bonhomme et al 2008).…”
Section: Genome Research 1929mentioning
confidence: 99%
“…The choice of d (and of the number of simulations) reflects to some extent a balance between computability and accuracy Marjoram et al 2003). In most ABC implementations the value of d is set as a quantile (the tolerance level P d ) from the empirical distance distribution found for a given observed data set, and typical values range from 10 À5 to 10 À2 (e.g., Estoup et al 2004;Becquet and Przeworski 2007;Fagundes et al 2007;Pascual et al 2007;Bonhomme et al 2008;Cox et al 2008). The quality of the ABC inference is expected to depend on the summary statistics, the distance metric, and the tolerance level P d used.…”
Section: T He Genetic Patterns Observed Today In Most Speciesmentioning
confidence: 99%